The olive constituent oleuropein exerts nephritic protective effects on diabetic nephropathy in db/db mice. (4th March 2022) - Liu, Yan; Dai, Wu; Ye, Shandong
Abstract: Background: Oleuropein, the most prevalent polyphenol in olives, exerts many positive impacts on human health, including counteracting cancer. However, the effect of oleuropein on diabetic nephropathy (DN) progression remains elusive. Methods: A total of three groups of mice were used in our study. Two groups of db/db mice fed with or without oleuropein. A group of wide-type mice fed with normal diet was used as normal control. After ten weeks of treatment, the body weight, biochemical parameters, oxidative stress markers, inflammatory cytokines levels, and kidney injury status were measured. Results: Our results demonstrated that oral administration of oleuropein reduced body weight, alleviated kidney injury, and decreased oxidative stress and inflammatory response in db/db mice. The oleuropein inhibited cell apoptosis via regulation of MAPK signalling pathways and its downstream targets Bax, caspase-3, and Bcl-2 expression. Conclusion: Oleuropein may server as a favourable additional agent for the treatment of patients with DN.